Mix design approaches of eco-friendly geopolymer concrete: A critical review - Mohammed Ali M. Rihan; Richard Ocharo Onchiri; Naftary Gathimba; Bernadette Sabuni (Hybrid Advances)
Geopolymer Concrete (GPC) is an innovative type of concrete that offers significant advancements in sustainability and environmental impact, particularly in the areas of recycling and alternative construction techniques. Geopolymers provide a sustainable and energy-efficient alternative to Portland cement binder for civil infrastructure applications. They have a low carbon footprint and can completely replace Portland cement. However, there is no established specification or standard for developing GPC mixes. This is partially due to the numerous variables that influence the production of GPC, including the properties of unprocessed materials, the kind and amount of the activator, and the cure program. This review study aims to provide a comprehensive and up-to-date analysis of the various methods used in the design of geopolymer concrete (GPC). This paper examines three different mix proportioning methodologies for GPC: the target strength, the performance approach, and statistical approaches. It is recommended to select a design method based on production conditions and GPC requirements.